1974
DOI: 10.1037/h0036547
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of intersensory transfer of form.

Abstract: The relative contributions of four sources of transfer in intersensory transfer between vision and touch were examined. Following a training task in identifying visually presented polygons or histoforms, six groups learned to make a motor switching response to tactually presented polygons in a transfer task. Transfer performance showed reliable evidence for the transfer of forward associations, minimal evidence for the transfer of stimulus learning, and no evidence for two types of nonspecific transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1977
1977
1981
1981

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Unfortunately, he neglected to deal with this point. It is noteworthy, that Shaffer and Ellis (1974) have recently described an experiment, using a paired-associate paradigm, in which the role of specific and nonspecific factors in the intersensory transfer of form between vision and touch was examined more completely than in our earlier report. They too, could uncover no evidence for a nonspecific transfer effect.…”
mentioning
confidence: 86%
“…Unfortunately, he neglected to deal with this point. It is noteworthy, that Shaffer and Ellis (1974) have recently described an experiment, using a paired-associate paradigm, in which the role of specific and nonspecific factors in the intersensory transfer of form between vision and touch was examined more completely than in our earlier report. They too, could uncover no evidence for a nonspecific transfer effect.…”
mentioning
confidence: 86%
“…Although none of these studies reported evidence of nonspecific transfer, their findings for specific transfer of form discrimination present a mixed picture. Whereas Clark et al (1972) found specific transfer from vision to touch and from touch to vision, under similar conditions Shaffer and his colleagues (Shaffer & Ellis, 1974;Shaffer & Howard, 1974) failed to obtain evidence of specific transfer in either direction. These findings are not easily interpreted, for all three studies employed a paired-associate paradigm.…”
mentioning
confidence: 97%
“…A number of studies have employed such transfer-of-training paradigms in the investigation of both specific and nonspecific cross-modal transfer effects (Clark, Warm, & Schumsky, 1972;Lobb, 1970;Pick, Pick, & Thomas, 1966;Shaffer & Ellis, 1974;Shaffer & Howard, 1974). Although none of these studies reported evidence of nonspecific transfer, their findings for specific transfer of form discrimination present a mixed picture.…”
mentioning
confidence: 99%
“…For example, Holmgren, Arnoult, and Manning (1966) had subjects learn a paired-associate label to a pattern in one modality (visual or auditory) and transfer this information to the opposing modality. Shaffer and Ellis (1974) used a similar task to examine transfer from vision to touch. Another paradigm for examining transfer of single pattern information across modalities has been the matching-to-sample task in which a subject receives a standard in one modality and a series of comparison stimuli in another modality and is required This research was supported by Grant 5R01 HD07163 from the National Institute of Child Health and Human Development.…”
mentioning
confidence: 99%